ROLE OF WOMEN IN THE IMPLEMENTATION OF THE NATIONAL GREENING PROGRAM (NGP) IN CEBU PROVINCE - Sarile, Teresita Cleopolda B.; Alburo, Rosalyn P.; Alburo, Hemres P.; Cutillas, Anesito L. (Journal of Agriculture and Technology Management, 2018)
Please see PDF file.